Advances in agronomy. - Sparks, Donald L., 1953- (Advances in agronomy, 2007)
Advances in Agronomy continues to be recognized as a leading reference and a first-rate source for the latest research in agronomy. As always, the subjects covered are varied and exemplary of the myraid of subject matter dealt with by thislong-running serial. Volume 92 contains four indespensable reviews and 17 detailed images.* Maintains the highest impact factor among serial publications in Agriculture * Presents timely reviews on important agronomy issues such as nutrients, water relations, polyacrylamide, and more* Enjoys a long-standing reputation for excellence in the field.